Unraveling a Rare Right-Sided Pleural Effusion in a Young Female: A Case of Pancreaticopleural Fistula - P. Prem Ananth; S. Raghul Raj; R. Anand; N. Nagarajan (Journal of Association of Pulmonologist of Tamil Nadu)
Pancreaticopleural fistula (PPF) is a rare complication of chronic pancreatitis, involving abnormal communication between the pancreatic duct and pleural cavity. It often presents with nonspecific respiratory symptoms, making diagnosis challenging. We report the case of a 33-year-old female with massive right-sided pleural effusion, which is uncommon in PPF. Treatment with antibiotics, chest drainage, and endoscopic retrograde cholangiopancreatography with stent placement led to symptom resolution. This case underscores the need to consider PPF in atypical pleural effusions.